2011
DOI: 10.2478/v10045-011-0023-y
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium Sporotrichioides Sherb. Toxins Evaluated in Cereal Grain with Trichoderma Harzianum

Abstract: Fusarium head blight is one of the most severe diseases of small grain cereals and is caused by several toxigenic Fusarium species. Yield losses and mycotoxin accumulation in grain are caused by the disease. F. sporotrichioides and F. poae produce type A trichothecenes. Saprophyte fungal antagonists, especially Trichoderma harzianum, are effective biocontrol agents against several fungal soil-borne plant pathogens. These fungal antagonists can reduce the production of Fusarium spp. mycotoxins in some crop plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…A unique strain from each species was used in the experiments ( Table 1). The species selected for analysis are ubiquitous ascomycetes recorded in numerous systems, and have been classified into two groups: F. fujikuroi, F. sporotrichioides and P. decumbens have been identified as plant, soil and grain pathogens (Yoshida et al, 1992;Brown and Gordon, 2001;Mateo et al, 2002;Wi sniewska et al, 2011;Swer et al, 2011); while A. strictum and P. chrysogenum are described as marine species in the WoRMS database (http://www.marinespecies. org) and have been isolated from the marine environment in previous studies (Costello et al, 2001;Julianti et al, 2011;An et al, 2013).…”
Section: Isolation and Taxonomic Identificationmentioning
confidence: 99%
“…A unique strain from each species was used in the experiments ( Table 1). The species selected for analysis are ubiquitous ascomycetes recorded in numerous systems, and have been classified into two groups: F. fujikuroi, F. sporotrichioides and P. decumbens have been identified as plant, soil and grain pathogens (Yoshida et al, 1992;Brown and Gordon, 2001;Mateo et al, 2002;Wi sniewska et al, 2011;Swer et al, 2011); while A. strictum and P. chrysogenum are described as marine species in the WoRMS database (http://www.marinespecies. org) and have been isolated from the marine environment in previous studies (Costello et al, 2001;Julianti et al, 2011;An et al, 2013).…”
Section: Isolation and Taxonomic Identificationmentioning
confidence: 99%
“…It was determined that Trichoderma harzianum produces a lytic enzyme, chitinase, which manifests antifungal activity against a wide range of fungal strains. It was found that non-toxigenic T.harzianum isolates significantly reduce the production of six types of A trichothecenes in cereals [38].…”
Section: Biological Factorsmentioning
confidence: 99%
“…can oxidize T-2 toxin into 3'-OH T-2 or 3'-OH HT-2 through the reaction of hydroxylation [14], but it was not certain if the products has the toxicity. Again, Trichoderma harzianum could reduce the acumination of T-2 toxin in crop by inhibiting the growth of pathogens, but it did not degrade T-2 toxin and patulin directly [15].…”
Section: Introductionmentioning
confidence: 95%